2021
DOI: 10.1126/sciadv.abi9031
|View full text |Cite
|
Sign up to set email alerts
|

Essay content and style are strongly related to household income and SAT scores: Evidence from 60,000 undergraduate applications

Abstract: There is substantial evidence of the relationship between household income and achievement on the standardized tests often required for college admissions, yet little comparable inquiry considers the essays typically required of applicants to selective U.S. colleges and universities. We used a corpus of 240,000 admission essays submitted by 60,000 applicants to the University of California in November 2016 to measure relationships between the content of admission essays, self-reported household income, and SAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 44 publications
4
57
0
Order By: Relevance
“…One of the challenges to increasing socioeconomic diversity across selective colleges may be that those institutions have historically evaluated applicants on criteria, including college entrance exam scores, extracurricular activities, and personal essays, that often, in part, reflect access to prior opportunities (Alvero et al, 2021; Rosinger et al, 2021). Furthermore, admission officers may lack the tools and resources to easily evaluate applicants in the context of their home, school, and neighborhood environments.…”
Section: Introductionmentioning
confidence: 99%
“…One of the challenges to increasing socioeconomic diversity across selective colleges may be that those institutions have historically evaluated applicants on criteria, including college entrance exam scores, extracurricular activities, and personal essays, that often, in part, reflect access to prior opportunities (Alvero et al, 2021; Rosinger et al, 2021). Furthermore, admission officers may lack the tools and resources to easily evaluate applicants in the context of their home, school, and neighborhood environments.…”
Section: Introductionmentioning
confidence: 99%
“…The uniform structure of the format of the college admissions essay, where every applicant has to respond to the same prompts with the same limits on word count for the same deadline, lends itself well to macro analyses of the actual text submitted by students. Recent studies using methods from machine learning have found that computational representations of admissions essays are strong predictors of applicant income [7,8], gender [8], and SAT score [9]. These studies were all similar in their "bag of words" approach to the data, where machine learning models were used to analyze word co-occurrence patterns across all of the documents.…”
Section: Background College Admissions Essaysmentioning
confidence: 99%
“…Self-reported household income (shortened to "income" hereafter) was also provided. Students reporting household incomes below $10,000 were suspected to have done so erroneously and excluded from analyses of income (see [9]). See Table 1 for summary statistics of the data.…”
Section: Datamentioning
confidence: 99%
“…There has been considerable concern around standardized tests in college and graduate admissions, yet there is growing evidence that many other metrics (e.g., letters of recommendation, essays), perceived as more equitable demonstrations of applicants' qualifications, are equally, if not more, prone to influence of family resources and income and can differentially impact applicants of different racial and gender groups (e.g., Alvero et al, 2021;Dalal et al, 2022).…”
Section: Commonly Used Criteria In Holistic Admissionsmentioning
confidence: 99%
“…Recent research shows that essays are not immune from the influence of family income either. Researchers at Stanford University (Alvero et al, 2021) found that essay content is strongly correlated with students' self-reported family income, and the correlation is even stronger than the association between SAT scores and household income. Essay content refers to the topics, diction, grammar, and punctuation in an essay.…”
Section: Essays or Personal Statementsmentioning
confidence: 99%